Practical soil protection and stabilization in Mediterranean viticulture - Llewellyn, C. A., (Cranfield University, Cranfield University at Silsoe, 2006)
The accelerated erosion of soil by water from Mediterranean hill-slopes under viticulture is a major problem. It is largely a result of the land management techniques employed and their influence on soil protection, structure and stability. Within this study, the relationships between viticulture practices, soil physical characteristics and erosion processes have been explored in detail, and a soil conservation strategy, which incorporates the use of herbicide managed cover, has been developed. The strategy was applied and tested in two established vineyards in southern France over a three year period (October 2001 to December 2004). Sediment and runoff losses were monitored at the plot scale from the date of treatment installation and comparisons were made with the losses from plots under conventional soil management. Cultivation, to produce a fine seedbed for cover establishment, encouraged soil to become hydrophobic and impeded drainage at depth. This aggravated soil losses under saturated conditions and impeded cover establishment. However, total sediment losses were reduced by the presence of a cover at both sites within the monitoring period. The results of a ‘Visual Soil Assessment’ showed that there was a measurable improvement in the physical condition of the soil of the vegetated plot three and a half years after the cover was sown. Controlled laboratory studies were conducted to identify the most suitable herbicide product and dose rate for inducing dormancy in a grass cover, whilst retaining its protective and stabilizing properties. Two products were tested: Paraquat and Glyphosate. At 21 days after treatment application, the treatment effects on plant and soil physical characteristics were assessed. Herbicide product and dose were found to indirectly influence a soil’s potential to erode but more detailed studies are required. Initial results suggest that Paraquat is the more suitable of the two products tested. The study concluded that herbicide managed permanent cover is a practical option for soil conservation in Mediterranean viticulture.